Premiers pêcheurs du littoral pacifique sud-américain - Danièle Lavallée; Michèle Julien (Les Nouvelles de l’Archéologie, 2008)
The Archaic fishermen and gatherers campsite at Quebrada de los Burros (Tacna, Peru) was occupied between ca. 10000 and 6000 B.P., during a calm and wet climate phase. The excavations revealed living-floor features (terraces, hearths and activity areas) and accumulations of food waste (fish, shells, crabs, terrestrial fauna). These remains demonstrate that, since the beginning, the inhabitants relied intensively on ocean resources. Lithic tools and bone instruments indicate diversified and sophisticated fishing and foraging techniques. According to sclerochronological analyses on shells and to terrestrial resources, it is turning out that it was possible to live all along the year in the same site. There is no evidence of an Andean origin of the first populations, and the possibility of a peopling from the North by a maritime way must be considered.